Analysis of Investment Decisions for Young Investors in Surabaya - Ira Wikartika; Ayundha Evanthi; Rahman Amrullah Suwaidi (Nusantara Science and Technology Proceedings, 2022)
Indonesians are aware of the value of saving money and placing financial security first. It is envisaged that through fostering a favorable investment environment, the majority of investors will be interested in using the convenience provided to invest their wealth. Investment is the act of putting money into assets by either individuals or businesses with the goal of earning significant returns in the future. When using the capital market as a venue to invest for specific financial goals, the role of investor behavior is crucial. Investment is the act of investing a sum of money into one or more assets over a specific time period with the hope of making a profit or seeing the value of the investment rise. Investors engage in investment activities in order to generate income or increase their rate of return on investment in the future. Decisions about investments are influenced by both rational and emotional factors. According to the prospect hypothesis, people do not always make rational judgments when faced with risk and uncertainty; instead, they can be swayed by psychological variables and irrational conduct. These psychological elements have an impact on investment and have an impact on the outcomes. By employing satisfaction as a mediating variable, this study examined the impact of investment literacy on young investors' decisions to purchase shares. Young investors who invest in a variety of securities firms in the city of Surabaya make up the respondents to this study. The findings of this study show that financial literacy has a direct impact on investors' investment contentment and decision-making and that investment satisfaction can mediate the relationship between investors' investment literacy and decision-making